PERTANGGUNGJAWABAN PIDANA PELAKU PELECEHAN SEKSUAL PENGIDAP FETISHISTIC DISORDER: STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 2286/PID.SUS/2020/PN SBY - Dwi Alfiyatussa Diyah; Ahmad Mahyani (Gapenas Publisher, 2022)
The purpose of this study is to identify and explain the criminal responsibility for perpetrators of sexual harassment with Fetishistic disorder also analyze the conformity of the criminal responsibility received by the perpetrators with Law Number 19 of 2016 on Information and Electronic Transactions. This research was using normative legal methods with statutory approach, conceptual approach originating from primary source in the form of statutory regulations, secondary and tertiary sources from related legal literature. The results of this study are the equating of Fetishistic disorder with the crime of sexual harassment in the form of obscenity as stated in the Criminal Code. The consideration used is the perpetrator's actions which clearly break the norms of decency. The actions taken by the perpetrator are carried out consciously and they know the impact of their actions. In accordance with article 44 of the Criminal Code, the perpetrators have to be responsible for their actions. Because the actions taken by the perpetrators involved technology so it will be a special kind of crime. Thus, the judge considered Article 27 paragraph (4) in conjunction with Article 45 paragraph (4) and/or Article 29 in conjunction with 45B of the Electronic Information And Transactions Law in deciding this crime